Juridical Review of The Act of Virtual Money Laundering - Yohanes Fiodas Jaman; Prija Djatmika; Abdul Madjid (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
The crime of money laundering as one type of white collar crime has actually been known since 1867. Cyber Money Laundering is money laundering carried out through cyberspace (